Dynamics of Strong Coupling Between Free Charge Carriers in Organometal Halide Perovskites and Aluminum Plasmonic States - Luo, Yang; Wang, Hai; Zhao, Le-Yi; Zhang, Yong-Lai (Frontiers in Chemistry, 2022)
We have investigated a strong coupled system composing of MAPbIxCl3-x perovskite film and aluminum conical nanopits array. The hybrid states formed by surface plasmons (SPs) and free carriers, rather than the traditional excitons, is observed in both steady-state reflection measurements and transient absorption spectra. In particular, under near upper band resonant excitation, the bleaching signal from the band edge of uncoupled perovskite was completed separated into two distinctive bleaching signals of the hybrid system, which is a clear evidence for the formation of strong coupling states between free carriers–plasmon state. Besides, a Rabi splitting up to 260 meV is achieved. The appearance of the lower bands can compensate for the poor absorption of the perovskite in the NIR region. Finally, we found that the lifetime of the free carriers–SPs hybrid states is slightly shorter than that of uncoupled perovskite film, which can be caused by the ultrafast damping of the SPs modes. These peculiar features on the strong coupled hybrid states based on free charge carriers can open new perspectives for novel plasmonic perovskite solar cells.